2015
DOI: 10.1177/0312896214565121
|View full text |Cite|
|
Sign up to set email alerts
|

A review of accounting research in the Asia Pacific region

Abstract: In this paper, we review scholarly accounting research published within the Asia Pacific Region by analysing nine of the main accounting journals within the region along five dimensions. The nine journals we focus on are: Accounting, Auditing and Accountability Journal; Australian Accounting Review; Abacus; Accounting and Finance; Australian Journal of Management; Accounting Research Journal; Journal of Contemporary Accounting and Economics; Managerial Auditing Journal; and Pacific Accounting Review. The five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 397 publications
2
85
0
1
Order By: Relevance
“…This research topic has been identified by Ripoll and Díaz (2014) within the research trends in the area of control and management, in which a total of 15 scientific articles had been identified for 2014 in the ISI Web of Knowledge, in high-impact scientific journals in the Web of Science. In this sense, Benson, Clarkson, Smith and Tutticci (2015), based on a review of academic accounting research journals in the Asia Pacific region, declare that said journals make a very significant contribution to research and its relationship to practice in the region and on an international level. In this same journal in 2014, the authors Olaya, Berbegal-Mirabent and Duarte conducted a bibliographic search up to 2010 on the main lines of research and future projection with regard to Technology Transfer Offices (TTOs), in which the authors acknowledge the need for UBRs and KT, focused on the work done by the TTOs, and anticipate future research related to the identification and quality of the services provided by the TTOs.…”
Section: Methodsmentioning
confidence: 99%
“…This research topic has been identified by Ripoll and Díaz (2014) within the research trends in the area of control and management, in which a total of 15 scientific articles had been identified for 2014 in the ISI Web of Knowledge, in high-impact scientific journals in the Web of Science. In this sense, Benson, Clarkson, Smith and Tutticci (2015), based on a review of academic accounting research journals in the Asia Pacific region, declare that said journals make a very significant contribution to research and its relationship to practice in the region and on an international level. In this same journal in 2014, the authors Olaya, Berbegal-Mirabent and Duarte conducted a bibliographic search up to 2010 on the main lines of research and future projection with regard to Technology Transfer Offices (TTOs), in which the authors acknowledge the need for UBRs and KT, focused on the work done by the TTOs, and anticipate future research related to the identification and quality of the services provided by the TTOs.…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on a similar study of accounting research in Asia-Pacific journals (Benson et al 2015). Following Benson et al (2015), modified where appropriate, this paper analyses the most cited papers in each of the five journals, as measured by total citations and by citations per year (total citations divided by the number of years since publication).…”
Section: South African Journal Of Business Management (Sajbm) and Soumentioning
confidence: 99%
“…First, further research is needed that expands on the existing body of accounting and finance research (Benson et al, 2015(Benson et al, , 2014 to show exactly how violations of planetary boundaries will translate into impacts on firms. Scientific evidence points out that the planetary boundaries are important collectively; consequently it appears that mechanisms should be developed to limit boundary violations.…”
Section: Future Research Agendamentioning
confidence: 99%